The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s21227521
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of Preretinal Space in Optical Coherence Tomography Images Using Deep Neural Networks

Abstract: This paper proposes an efficient segmentation of the preretinal area between the inner limiting membrane (ILM) and posterior cortical vitreous (PCV) of the human eye in an image obtained with the use of optical coherence tomography (OCT). The research was carried out using a database of three-dimensional OCT imaging scans obtained with the Optovue RTVue XR Avanti device. Various types of neural networks (UNet, Attention UNet, ReLayNet, LFUNet) were tested for semantic segmentation, their effectiveness was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…Since the studies included in this review solely reported either PSNR or SNR of the denoised images in comparison to multiple reference tests, it remains uncertain whether DL provides significant assistance in image denoising and speckle reduction. Ideally, the impact of DL for denoising OCT images in ophthalmology should be demonstrated in practice-based settings and validated by its ability to improve further objectives such as detection [60], classification [61], and segmentation [62], which the majority of included studies did not consider.…”
Section: Discussionmentioning
confidence: 99%
“…Since the studies included in this review solely reported either PSNR or SNR of the denoised images in comparison to multiple reference tests, it remains uncertain whether DL provides significant assistance in image denoising and speckle reduction. Ideally, the impact of DL for denoising OCT images in ophthalmology should be demonstrated in practice-based settings and validated by its ability to improve further objectives such as detection [60], classification [61], and segmentation [62], which the majority of included studies did not consider.…”
Section: Discussionmentioning
confidence: 99%
“…Deep neural networks are also suitable for effective segmentation of the preretinal space [ 3 ]. In this case, effective segmentation of the posterior cortical vitreous (PVC) and inner limiting membrane (ILM) is required.…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…In the image segmentation task, the Dice coefficient will be more sensitive to the segmentation internal data, while the Hausdorff distance is sensitive to the segmentation boundary data. The Hausdorff distance calculation formula is derived from Formula (10), Formula (11), Formula (12).…”
Section: Evaluation Indicatorsmentioning
confidence: 99%
“…Recently, deep learning has achieved remarkable results in visual image recognition tasks. 12 The application of image segmentation in medicine can mark the lesions and extract features for diagnosis and treatment. The deep convolutional network has better applications in medical image segmentation.…”
Section: Introductionmentioning
confidence: 99%